An Analysis of Text Readability in 9th Grade English Textbook Using FRE Formula on Readable Software - Putri Rafa Salihah; Sahiruddin Sahiruddin; Putu Dian Danayanti Degeng (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2019)
AbstractThis study measured the readability level of reading texts in English textbook. This study used a text level complexity approach and used quantitative method by utilizing Flesch Reading Ease formula by Rudolph Flesch and calculate by software www.readable.com. The purpose of this study is to find out the readability level of reading texts in English textbook entitled “Bahasa Inggris Think Globally Act Locally SMP/MTs Kelas IX junior high school Published by the Ministry of Education and Culture of Indonesia”. The textbook is revised in 2018 of curriculum 2013. The source of the data in this study were 35 reading texts divided into four levels are: Fairly Difficult, Standard, Fairly Easy, and Easy. While the data in this study were 7 reading texts taken purposively (procedure text, narrative text and report text). The result showed that the textbook is not readable to IX grade of Junior High School. By a final average of71.54 is "Fairly Easy level" level between 70 to 80 for grade VII. Meanwhile, for grade IX should be at average amount of 60 to 70 at “Standard” level. Thus, the analysis of readability level of English textbook is needed in education world. As the best contribution and information for school institution in Indonesia. Keywords: Readability, Textbook, Flesch Reading Ease AbstrakPenelitian ini mengukur tingkat keterbacaan teks bacaan dalam buku teks bahasa Inggris. Penelitian ini menggunakan pendekatan tingkat kompleksitas teks dengan menggunakan metode kuantitatif dengan rumus Flesch Reading Ease oleh Rudolph Flesch dan dihitung oleh perangkat lunak www.readable.com. Tujuan dari penelitian ini adalah untuk mengetahui tingkat keterbacaan teks bacaan dalam buku teks Bahasa Inggris yang berjudul "Bahasa Inggris Think Globally Act Local SMP / MTs Kelas IX SMP yang Diterbitkan oleh Kementerian Pendidikan dan Kebudayaan Indonesia". Buku teks tersebut direvisi pada tahun 2018 dengan kurikulum 2013. Sumber data dalam penelitian ini adalah 35 teks bacaan yang dibagi menjadi empat tingkatan adalah: Cukup Sulit, Standar, Cukup Mudah, dan Mudah. Sementara, data dalam penelitian ini adalah 7 teks bacaan yang diambil secara purposif (teks prosedur, teks naratif dan teks report). Hasil penelitian menunjukkan bahwa buku teks tidak dapat dibaca untuk kelas IX SMP. Dengan rata-rata akhir 71,54 adalah tingkat "Cukup Mudah" level antara 70 hingga 80 untuk kelas VII. Sementara itu, untuk kelas IX harus memiliki jumlah rata-rata adalah 60 hingga 70 berlevel "Standar". Dengan demikian, analisis tingkat keterbacaan buku teks bahasa Inggris sangat dibutuhkan dalam dunia pendidikan. Sebagai kontribusi dan informasi terbaik untuk institusi sekolah di Indonesia.Kata Kunci: Keterbacaan, Buku Teks, Flesch Reading Ease